Hak Tanggungan Secara Cross Collateral dalam Penyaluran Kredit - Mohammad Wendy Harmansyah; Dudik S; Subekti Subekti (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The law must be able to provide adequate protection against variations in the provision of collateral for credit facilities. This variation and legal protection relates, among others, to the existence of cross collateral in credit collateral. The type of research or approach taken is empirical legal research while the nature of the research carried out is categorized as descriptive-analytical research. Required special rules governing cross collateral. This is necessary to provide legal certainty and legal protection for both creditors and debtors in entering into credit agreements, especially if the agreements use cross collateral collateral.